Critical perspectives on predictive policing: anticipating proof? - Galis, Vasilis; Gundhus, Helene Oppen; Vradis, Antonis (Edward Elgar Publishing, 2025)
"'This book provides rich empirical and thoughtful conceptual analyses. With its STS-inspired, international, interdisciplinary as well as critical approach, it contributes significantly to the debate on predictive policing, which is still incomplete despite numerous related publications.' - Simon Egbert, Bielefeld University, Germany"--